Impact of occupational sedentary behavior on mental health: A systematic review and meta-analysis - Hijrah Nasir; Martine Duclos; Reza Bagheri; Alistair Cole; Julien S. Baker; David Thivel; Frédéric Dutheil (PLoS ONE, 2025)
Background Despite numerous meta-analyses on the effects of leisure time sedentary behavior, the effect of sedentary behavior at work on mental health is largely under debate. We aimed to systematically identify and synthetize the literature examining the association between sedentary behavior at work on mental health. Method PubMed, Embase, Cochrane, and Psycinfo databases were searched for articles reporting risks for mental health due to occupational sedentary behavior. We computed random-effects meta-analysis using all risks and both intermediate and severe levels of mental health issues, following by sensitivity analysis on severe mental health issues using 1) all risks, then only 2) fully adjusted and 3) crude or less adjusted lowest risks (pessimistic models), and 4) fully adjusted and 5) crude or less adjusted highest risks (optimistic models). We conducted meta-regression on possible influencing factors. Results We included 12 studies in the systematic review and 7 in the meta-analysis, for a total of 40,314 workers (35 years old, 65.5% men). Exposure to sedentary behavior at work increased the risk of intermediate and severe mental health issues by +34% (95 CI 18–49%). All sensitivity analyses on severe mental health issues were also significant, whatever the model: + 35% (12–58%) using all risks, 39% (15–63%) using fully adjusted pessimistic model, + 36% (13–59%) using crude or less adjusted pessimistic model, 85% (27–143%) using fully adjusted optimistic model, + 85% (26–143%) using crude or less adjusted optimistic model. Age may have an increased risk of mental health issue when exposed to occupational sedentary behavior, while high education reduced the risk. Conclusion Our meta-analysis shows that occupational sedentary behavior increases the risk of mental health issue. Inconsistent results precluded robust conclusion for variables that may further influence this risk.